Implementasi Brain Gym Pada Lansia Demensia Dengan Gangguan Memori Di Pusat Pelayanan Sosial Lanjut Usia: Implementasi Brain Gym Pada Lansia Demensia - Sulfi Sulfi; Bahriah Bahriah; Yenny Djeny Randa (Nursing Practice Journal, 2025)
A person with dementia has impaired intellectual function, disrupting daily activities and relationships with people around them. Loss of intellectual capacity in dementia is not only memory, but also cognitive and personality. This study aims to determine the effect of brain gymnastics (brain gym) on the level of dementia in the elderly. The research method used in this case study is a descriptive method with case presentation. The research subjects were two respondents. The study results were that after nursing intervention for 3x8 hours, the results were obtained for patient 1 after brain gymnastics Brain gym elderly patient said they had progress after doing gymnastics, while patient II elderly, said they remembered the little movement given. Given the importance of brain gymnastics in elderly dementia with memory disorders, it is hoped that care will be needed to manage patients with brain gymnastics. This study can be developed and can think critically about the theoretical basis of brain gymnastics in dementia patients, so that it is much deeper in providing comprehensive nursing care